2022
DOI: 10.1093/ofid/ofac457
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic and Sedative Medications Are Associated With Neurocognitive Performance of Well Treated People With Human Immunodeficiency Virus

Abstract: Background We previously showed that anticholinergic (ACH) medications contribute to self-reported neurocognitive impairment (NCI) in elderly people living with HIV (PLWH). The current cross-sectional study further evaluated the effect of ACH and sedative drugs on neurocognitive function in PLWH who underwent comprehensive neuropsychological evaluation. Methods A medication review was performed in PLWH enrolled in the prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…There are some data showing associations between their use and self-reported [19,22] and objective cognitive impairment [17,20,23]. Consistent with our findings, Jakeman et al identified most ACMs used by those aged >65 years within the Swiss HIV Cohort Study (SHCS) [19] and subsequently a subset of those aged >45 years of the SHCS who underwent formal cognitive testing [20], as being of low anti-cholinergic potential. Looking at the use of ACMs and other "neurocognitive adverse effect medications", Psomas et al recently reported a relationship between ACM use and falls in a cohort of women with HIV in the USA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There are some data showing associations between their use and self-reported [19,22] and objective cognitive impairment [17,20,23]. Consistent with our findings, Jakeman et al identified most ACMs used by those aged >65 years within the Swiss HIV Cohort Study (SHCS) [19] and subsequently a subset of those aged >45 years of the SHCS who underwent formal cognitive testing [20], as being of low anti-cholinergic potential. Looking at the use of ACMs and other "neurocognitive adverse effect medications", Psomas et al recently reported a relationship between ACM use and falls in a cohort of women with HIV in the USA.…”
Section: Discussionsupporting
confidence: 90%
“…Literature on the association between ACM use and age-related co-morbidities among people living with HIV is sparse. There are some data showing associations between their use and self-reported [19,22] and objective cognitive impairment [17,20,23]. Consistent with our findings, Jakeman et al identified most ACMs used by those aged >65 years within the Swiss HIV Cohort Study (SHCS) [19] and subsequently a subset of those aged >45 years of the SHCS who underwent formal cognitive testing [20], as being of low anti-cholinergic potential.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most studies were single centre 22,29,31–33,39–42,44,45,48–52,54,57,59–66 and conducted in Europe. 13,19,28,30–33,39,41,43–51,53,56–63,65,67 The sample size ranged from 2 to 1292 participants, and the population was majority male. Twenty-eight studies were cross-sectional, 19,27,28,30–33,39–41,44,45,47–51,53,55,56,61–67 3 were prospective cohort studies, 43,46,57 3 were prospective intervention studies with no control group, 22,59,60 2 nonrandomized controlled studies, 42,52 and 1 randomized controlled study, 58 1 case–control study, 29 and 1 case-report.…”
Section: Resultsmentioning
confidence: 99%
“…13,19,28,30–33,39,41,43–51,53,56–63,65,67 The sample size ranged from 2 to 1292 participants, and the population was majority male. Twenty-eight studies were cross-sectional, 19,27,28,30–33,39–41,44,45,47–51,53,55,56,61–67 3 were prospective cohort studies, 43,46,57 3 were prospective intervention studies with no control group, 22,59,60 2 nonrandomized controlled studies, 42,52 and 1 randomized controlled study, 58 1 case–control study, 29 and 1 case-report. 54 In most studies, investigators used explicit criteria (Table 1), and in others, implicit criteria or a combination of both (Table 2).…”
Section: Resultsmentioning
confidence: 99%